Vie et moments d’une gare: le Musée d’Orsay entre projet muséographique et projet curatorial (1980-1986) - Martellini, Matilde (Opus Incertum, 2024)
This contribution explores the episode of the reconfiguration of the Orsay station, focusing particularly on the role of Gae Aulenti and her museographic project. Aulenti’s approach employed compositional elements that were both a source of critique and the foundation of the museum's unique identity. By examining newly available documents from the Archives Nationales de France and the Musée d’Orsay Documentation and Library, this study reconstructs the genesis of the Parisian museum project. Aulenti’s work at the Orsay reveals the profound confrontation between curatorial practices, architecture, and cultural policy underlying the project. A deeper understanding of her intervention requires the identification of possible exchanges between her broader professional experience and the demands of the Orsay project. This contribution seeks to trace a common thread between the various disciplines of spatial design in which Aulenti worked, in order to establish a link between her experience in the world of temporary exhibitions, theatrical scenography, and museographic installation, between the ephemeral and the permanent.